Five-Year Long-Term Follow-Up of Selective Laser Trabeculoplasty in Open-Angle Glaucoma - Gack, Christina; Lämmer, Robert; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose Selective laser trabeculoplasty (SLT) is known as a safe laser therapy for an effective reduction in intraocular pressure (IOP). The aim of this study was to examine the therapeutic success of SLT in open-angle glaucoma (OAG) patients with a long-term follow-up of 5 years. Methods Forty-six eyes of forty OAG patients, some with previous intraocular surgery, underwent SLT (24 males, 16 females). Therapeutic success was categorized as: category (I) - IOP reduction <= 21 mmHg and > 20% compared to baseline IOP with additional glaucoma medication; category (II) - IOP reduction <= 18 mmHg and > 30% compared to baseline IOP with additional glaucoma medication; category (III) - IOP reduction <= 18 mmHg without any additional glaucoma medication at all follow-ups. Therapeutic failure was defined as the necessity of any further glaucoma surgery (IV). Results (1) SLT was well tolerated in all eyes, and no severe side effects or complications were recorded. (2) After 1-year follow-up, therapeutic success was 27% (I), 30% (II), and 3% (III). The therapeutic failure rate was 40% (IV). (3) After 2 years follow-up, therapeutic success was 7% (I), 10% (II), and 0% (III). The therapeutic failure rate was 83% (IV). (4) After 3 years follow-up, the therapeutic failure rate increased up to 100% (IV). Conclusion SLT seemed to be effective in lowering IOP in the first year in the present cohort, however, the long-term effect is low and additional local therapy or surgical interventions are necessary.
CRIS-Team WoS Importer:2021-12-31